Marketing airports to facilitate the development of tourism - Halpern, Nigel (Henry Stewart Talks, 2009)
The importance of tourism, Different types of airlines that serve tourist markets and their needs, The tourism related airport marketing mix, Key features of the airport product, Promotional techniques that can be used to create awareness, Price incentives and marketing support, Distribution channels
Archived at 2022/04/04